SIRT3 mediates CPT2 delactylation to enhance mitochondrial function and proliferation in goat granulosa cells - Shuaifei Song; Mingzhi Yang; Jiayue Li; Yaru Li; Lei Wang; Shiyi Yao; Zihan Wang; Qiuyan Li; Yanguo Han; Dejun Xu; Zhongquan Zhao (Journal of Animal Science and Biotechnology)
Abstract Background Reproductive efficiency in goats is closely linked to the healthy development of follicles, with the proliferation of ovarian granulosa cells (GCs) playing a crucial role in this process. Sirtuin 3 (SIRT3), an enzyme that catalyzes post-translational modifications (PTMs) of proteins, is known to regulate a variety of mitochondrial metabolic pathways, thereby affecting cell fate. However, the specific effect of SIRT3 on the follicular development process remains unclear. Therefore, this study aimed to investigate the regulatory role of SIRT3 in the mitochondrial function and proliferation of goat GCs, as well as the underlying mechanisms involved. Results In this study, GCs from small follicles in goat ovaries presented increased proliferative potential and elevated SIRT3 expression levels compared with those from large follicles. In vitro, SIRT3 overexpression enhanced mitochondrial function, promoted proliferation and inhibited apoptosis in GCs. Correspondingly, the inhibition of SIRT3 led to the opposite effects. Notably, SIRT3 interacted with carnitine palmitoyl transferase 2 (CPT2) and stabilized the CPT2 protein by mediating delactylation, which prolonged the half-life of CPT2 and prevented its degradation. Further investigation revealed that CPT2 overexpression enhanced fatty acid β-oxidation and mitochondrial function in GCs. Additionally, CPT2 promoted the proliferation of GCs by increasing the protein levels of β-catenin and its downstream target, cyclin D1 (CCND1). However, this effect was reversed by 3-TYP (a SIRT3 inhibitor). Conclusions SIRT3 stabilizes CPT2 protein expression through delactylation, thereby enhancing mitochondrial function and the proliferative capacity of GCs in goats. This study provides novel insights into the molecular mechanisms and regulatory pathways involved in mammalian follicular development. Graphical Abstract